(untitled) (Surkhet Journal, 2014)
Nepal has the history of more than eight decades of science teaching/ learning at the higher-level education.‌It‌ started‌ in‌ 1934‌ in‌ Tri-chandra‌ College‌ at‌ proficiency‌ level.‌‌This‌ paper‌ tries‌ to‌ analyze‌ the present status and challenges of science education in Tribhuvam University. It is found that science education has only 3.60 % share of total students’ enrollment in constitute campuses of TU. It is also found‌ that‌ there‌ is‌ an‌ association‌ between‌ enrollment‌ of‌ male‌ and‌ female‌ students‌ in‌ constituent/‌‌‌‌afiliated‌ science campuses.